2020
DOI: 10.1111/ced.14218
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐ and gender‐associated clinical and psychosocial characteristics of patients with psoriasis

Abstract: Background. Sex and gender may affect disease prevalence, adverse effects and response to therapy. Aim. To analyse sex and gender differences in outpatients with psoriasis. Methods. A cross-sectional study was conducted at IDI-IRCCS, Rome, over a 3-year period. In total, 3023 patients with psoriasis were enrolled. Anthropometric and demographic characteristics were recorded, and a dermatologist evaluated the clinical severity of disease. Quality of life (QoL) questionnaires were collected. Univariate and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 25 publications
3
30
0
Order By: Relevance
“…Moreover, linear regression analysis demonstrated that gender inequality showed a slight inclination to countries with higher socioeconomic status. Usually, females suffered a more significant physical and psychosocial impact of psoriasis on life quality than males (14)(15)(16). Researches showed that even though the clinical manifestations were lighter than in males, females bore more significant psychological distress and a higher probability of anxiety or depression (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, linear regression analysis demonstrated that gender inequality showed a slight inclination to countries with higher socioeconomic status. Usually, females suffered a more significant physical and psychosocial impact of psoriasis on life quality than males (14)(15)(16). Researches showed that even though the clinical manifestations were lighter than in males, females bore more significant psychological distress and a higher probability of anxiety or depression (14).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, females suffered a more significant physical and psychosocial impact of psoriasis on life quality than males (14)(15)(16). Researches showed that even though the clinical manifestations were lighter than in males, females bore more significant psychological distress and a higher probability of anxiety or depression (14). Among psoriasis patients, females may be more prone to perceive stress and may be more likely to perceive a more significant mental impact.…”
Section: Discussionmentioning
confidence: 99%
“…Although male gender is an established risk factor for severe COVID-19, females may be more susceptible to indirect excess morbidity from the pandemic. Further investigation into sex-specific variation in clinical manifestations of mental health disorders, likelihood of reporting worsening psoriasis, differences in baseline severity and responses to systemic therapy is thus warranted 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion of the 1002 patients enrolled in the phase 3 BE VIVID and BE READY trials were male (71.8%) and white (82.1%). It has been suggested that male patients generally have greater severity of psoriasis [35], leading to a greater proportion being included in the trials; however, another study has indicated that female patients experience greater impact on their quality of life [36], and the vast majority of clinical trials exclude pregnant women, meaning that they do not appear in true proportion [37]. Additionally, while the majority of patients in the general moderate to severe psoriasis disease population are white, this study Fig.…”
Section: Discussionmentioning
confidence: 72%